Assessment of Pavement Structural Strength by the Falling Weight Deflectometer - Andrus Aavik (The Baltic Journal of Road and Bridge Engineering, 2006)
The main objective of the research project was to derive the equation for calculating the pavement equivalent E-modulus on the basis of the Falling Weight Deflectometer (FWD) deflection measurement data to be used in the Estonian Pavement Management System (EPMS) for network and project level analysis so, that the determined values are comparable with the Estonian flexible pavement design procedure 2001-52. In 1999, 32 and in 2001 additional 19 FWD test sites were chosen on actual pavement structures to perform FWD measurements annually, once or twice per month from early spring until late autumn. FWD measurement data were analysed mathematically and the results were compared with the Estonian flexible pavement design procedure. The research project results in the following: • The quantitative methodology for evaluating the qualitative characteristics of the pavement is determined on the basis of the Cobb-Douglas equation, taking into account at a time practically an unlimited number of factors influencing the pavement structural condition. • The relationship between the pavement equivalent elastic modulus calculated according to the Estonian flexible pavement design procedure 2001-52 and based on the FWD measured deflection is determined. The equation for calculating of the pavement equivalent E-modulus on the basis of the FWD deflection data to be used in the EPMS is derived.